1997
DOI: 10.1523/jneurosci.17-20-07626.1997
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of IPSCs by Endogenous Calcineurin Activity

Abstract: Synaptic inhibition, mediated by GABA A receptors, regulates neuronal firing, influences coincidence detection (Kö nig et al., 1996), and can synchronize the output of neural circuits (Cobb et al., 1995). Although GABA A receptors can be modulated by phosphorylation, few studies have directly addressed the role of such modulation at synapses, where the nonequilibrium conditions of receptor activation are quite different from those often used to study GABA A receptors in vitro. Here we promoted endogenous phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
137
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 49 publications
(80 reference statements)
12
137
3
Order By: Relevance
“…The final illustration of the cellular and molecular mechanisms underlying bidirectional regulation of GABA A receptors mediated by kinases and phosphatases in synaptic plasticity can teach us much about what kinds of molecules are needed to build arrays of the GABA A receptor regulations. CaN is reported to modulate the channel kinetics of the GABA A receptors in cultured neurons (Jones and Westbrook, 1997). However, we found that there were no changes of the unitary GABA A R-IPSC rise times or their decay time constants after activation of CaN.…”
Section: Discussioncontrasting
confidence: 62%
“…The final illustration of the cellular and molecular mechanisms underlying bidirectional regulation of GABA A receptors mediated by kinases and phosphatases in synaptic plasticity can teach us much about what kinds of molecules are needed to build arrays of the GABA A receptor regulations. CaN is reported to modulate the channel kinetics of the GABA A receptors in cultured neurons (Jones and Westbrook, 1997). However, we found that there were no changes of the unitary GABA A R-IPSC rise times or their decay time constants after activation of CaN.…”
Section: Discussioncontrasting
confidence: 62%
“…This depression recovered within 1 h after Sp-cAMPS was washed out with normal ACSF (data not shown). This result drew our attention to involvement of inhibitory synaptic transmission in Sp-cAMPS-induced LTP and to the modulation of GABA A receptors by phosphorylation (21,22). We therefore examined the effect of Sp-cAMPS on synaptic transmission in the presence of picrotoxin, a GABA A receptor antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…Other evidence also suggests that activation of protein phosphatases favors the induction of LTD, whereas activation of protein kinases such as PKA, CaMK (calcium calmodulin kinase)-II, or CaMKIV promotes LTP (6,40). Furthermore, modulations of GABA A receptors by PKA and protein phosphatases can eliminate and enhance the inhibitory function of GABA A receptors, respectively (21,22). It is therefore possible that PKA-activated phosphorylation of both GABA A and AMPA receptors can subsequently inhibit activation of protein phosphatases, ensuring that the direction of synaptic plasticity is primarily toward potentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The size and duration of excitatory and inhibitory postsynaptic potentials are largely determined by transmitter release and postsynaptic channel kinetics (15,(22)(23)(24). Modulation of kinetics is an important mechanism to modulate synaptic transmission (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%